1996
DOI: 10.1177/0146167296226003
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Discrimination in Positive and Negative Outcome Allocations: Impact of Stimulus Valence, Relative Group Status, and Relative Group Size

Abstract: Three studies investigated the determination of social discrimination by the valence of stimuli that are allocated between groups. The studies were based on either the minimal group paradigm or a more reality-based laboratory intergroup setting, with stimulus valence, group status, and group size as factors and with pull scores on Taifel matrices as dependent variables. In general, the results showed that group members did not discriminate against the out-group when allocating negative stimuli, where as for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 28 publications
6
105
1
Order By: Relevance
“…Instead, when participation in intragroup cooperation and intergroup competition costs the same and provides the same absolute benefits to the in-group, group members strongly prefer intragroup cooperation to intergroup competition. The present experiments suggest that this preference for peaceful coexistence may be limited to relations between groups of equal status and power (Otten, Mummendey, & Blanz, 1996;Scheepers et al, 2006). When group members were put in a disadvantaged position relative to an out-group, either by the competitive behavior of the outgroup or by bad luck, they competed against the out-group to a considerable extent.…”
Section: Discussionmentioning
confidence: 62%
“…Instead, when participation in intragroup cooperation and intergroup competition costs the same and provides the same absolute benefits to the in-group, group members strongly prefer intragroup cooperation to intergroup competition. The present experiments suggest that this preference for peaceful coexistence may be limited to relations between groups of equal status and power (Otten, Mummendey, & Blanz, 1996;Scheepers et al, 2006). When group members were put in a disadvantaged position relative to an out-group, either by the competitive behavior of the outgroup or by bad luck, they competed against the out-group to a considerable extent.…”
Section: Discussionmentioning
confidence: 62%
“…The majority of studies demonstrating the PNAE in adults have been conducted using between-subjects designs (Blanz et al, 1995;Otten et al, 1996), while the findings obtained in within-subject designs have not been similarly straightforward. For example, Wenzel and Mummendey (1996) found the PNAE only on 'pure' lists of traits, when participants evaluated the groups only with regard to either positive or negative traits (i.e., between-subjects).…”
Section: Studymentioning
confidence: 99%
“…In this account positive distinctiveness can be created independently of the valence of the attributes to be assigned. Recent research has shown that us-them categorization results in less social discrimination when negative rather than positive attributes are allocated between groups (Blanz, Mummendey, & Otten, 1995;Buhl, 1999;Gardham & Brown, 2001;Otten, Mummendey, & Blanz, 1996). This phenomenon has been termed the 'positive-negative asymmetry effect' (PNAE: Mummendey et al, 1992).…”
mentioning
confidence: 99%
“…Several studies have noted that children are sometimes more willing to differentiate between groups on positive attributes and much less reliably show intergroup discrimination on negative attributes (e.g., Bennett et al, 2004;Bennett, Lyons, Sani & Barrett, 1998;Bigler, Jones & Lobliner, 1997;Bigler, Brown & Markell, 2001). This phenomenon has been termed the dpositive-negative asymmetry effectT (PNA effect: Mummendey & Otten, 1998;Mummendey et al, 1992;Otten, Mummendey & Blanz, 1996). However, studies that have noted the PNA effect typically involved children aged 6 years and above.…”
Section: Introductionmentioning
confidence: 99%